Deceiving The Myths of Nanotechnology in Relation to Nanotoxicity: Pharmaceutical Science-Pharmacy - Begum, Jeenatara; Chakraborty, Tamalika; Sahoo, Pramit; Roy, Pritam; Bhakta, Sebabrata (International Journal of Life Science and Pharma Research, 2023)
The toxicity of nanoparticles (NPs) is a critical research topic in nanotechnology, as it is essential to understand thehazards posed by the wide spectrum of NPs that vary in shape, size, and composition. Previous reviews have yet to thoroughlyexplore the Biological Effective Doses of NPs, which drive toxicity and are influenced by factors such as solubility, charge, shape,contaminants, and the ability of NPs to translocate from the deposition site in the lungs. This review aims to fill the gap in theliterature by providing an overview of the possible toxicity of nanoparticles in zebrafish during growth stages, with a focus onoxidative stress, and exploring the available modes of toxicity that are relevant to conventional pathogenic particles. This reviewalso discusses the effects of nanomaterials on the reproductive system in animal models, providing insight into the potential toxicityof nanoparticles in humans. This review aims to provide a comprehensive overview of the toxicity of nanoparticles and to criticallyexplore the challenges associated with implementing nanotechnology, particularly in the pharmaceutical development of noveltherapeutic products and regulatory issues. The review also considers recent uses and projected nanotechnology advancements,providing a basis for future research in this field. In conclusion, this review rectifies the lacunae in previously published reviews byproviding a comprehensive overview of the toxicity of nanoparticles and exploring the challenges associated with implementingnanotechnology. The aim and objective of this review are to provide a comprehensive understanding of the toxicity of nanoparticlesand to guide future research in this field.